If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36x + -24 = 0 Reorder the terms: -24 + 36x = 0 Solving -24 + 36x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 36x = 0 + 24 Combine like terms: -24 + 24 = 0 0 + 36x = 0 + 24 36x = 0 + 24 Combine like terms: 0 + 24 = 24 36x = 24 Divide each side by '36'. x = 0.6666666667 Simplifying x = 0.6666666667
| 2(y+7)=3(y-2) | | y=1/2-100 | | x+0.75=0.25 | | -5x+4x-6=21 | | 14-2w=18w-20 | | 2a-2.5=8.5 | | y+11X=0 | | 5-6n^2=-19 | | 0.6+z=30 | | -5x+4x+6=21 | | 1.80=1+0.05*12 | | (10x+2)2=(15x+19) | | 17x+8+11x+4=180 | | 1.80=1+0.05x | | 8/15/n=2/3 | | 5(4+3x)-9=-31 | | 2x^2-30x=-5x^2-3x-18 | | s+9=-27 | | 2.1x+4.2y=14.7 | | 2*4x*3y-4x+7y= | | 10/2420/24 | | (6x-55)=(3x-16) | | (X+3)(2x-8)= | | 7a^2+64a+64=0 | | 5(4+3x)-9=31 | | 4x^2=620 | | 12x(x-20)=-48 | | 2p^2-10p+9=0 | | (7x-6)=(3x+14) | | 6x^2+6x-14=49-41x | | 4=6/(2x-3) | | 8(3x+1)=1 |